Performance of LTE network for VoIP users. (1st January 2012) - Asheralieva, Alia; Khan, Jamil Y.; Mahata, Kaushik
With the arrival of LTE standard, it is expected that the mobile voice services paradigm will shift from the circuit switched to fully packet switched mode supporting the VoIP services. VoIP services took quite a bit of time before they were accepted as the main stream telephony service in the fixed networks. To provide VoIP services over the LTE networks with appropriate QoS, it is necessary to analyse the performance of such services and optimise the network parameters. This paper analyses the performance of VoIP services on the LTE network using the FD and the SMP packet scheduling techniques. This work identifies and analyses the features of above LTE packet scheduling techniques to enhance the QoS of VoIP services. An OPNET-based simulation model is used to analyse the performance of VoIP services on the LTE network by incorporating G.711 and G.723 speech coders. The work also studied the performance of VoIP services in variable transmission channel conditions.